Critical Metrics and Fundamental Materials Challenges for Renewable Hydrogen Production Technologies. Issue 1669 (29th October 2014) - Turner, J.; Miller, Eric L.; Peterson, David; Randolph, Katie; Ainscough, Chris
ABSTRACT The US Department of Energy’s (DOE) Fuel Cell Technologies Office has made significant progress in fuel cell technology advancement and cost reduction. Encouragingly, rollouts of fuel-cell vehicles by major automotive manufacturers are scheduled over the next several years. With these rollouts, enabling technologies for the widespread production of affordable renewable hydrogen becomes increasingly important. Near-term utilization of current reforming and electrolytic processes is necessary for early hydrogen markets, but transitioning to industrial-scale renewable hydrogen production remains essential to the longer term. Central to the long term vision is a portfolio of renewable hydrogen conversion processes, including, for example, the direct photoelectrochemical and thermochemical routes, as well as photo-assisted electrochemical routes. DOE utilizes technoeconomic analyses to assess the long-term viability of these emerging hydrogen production pathways and to help identify key materials- and system-level cost drivers. Sensitivity analysis from the technoeconomic studies will be discussed in connection with the metrics and fundamental materials properties that have direct impact on hydrogen cost. It is clear that innovations in macro-, meso- and nano-scale materials are all needed for pushing forward the state-of-the-art. These innovations, along with specific research and development pathways for advancing materials systems for the renewable hydrogen conversion technologies are discussed.